«Տօն քառասնօրեայ գալստեանն Քրիստոսի ի տաճարն» անուան ծագման շուրջ - Նանեան, Բաբկէն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Следуя по стопам Иерусалима, Армянская Церковь первой приняла новообразованный праздник Сретения. Первоначально известное как «Сороковой день от Епифании», это торжество позже, вероятно Исихием Иерусалимским, было переименовано в «Сретение». Это новшество было встречено блестящей армянской адаптацией «Տեառնընդառաջ». Тем не менее, церковные деятели, очевидно не были в достаточной степени удовлетворены или же в силу насущной необходимости были вынуждены предложить новое, не имеющее анало- гов, название праздника, в виде «Пришествие сорокадневного Христа вхрам». Наиболее убедительным объяснением такого рода действий могла быть неминуемая угроза со стороны несториан, активно действовавших на юге Армении, которые яростно отвергали божественную природу Иисуса. Following the footsteps of Jerusalem, the Armenian Church was first to accept the newly founded feast of Presentation of Jesus in the Temple. Initially known as “Fortieth day of Epiphany”, this solemnity later on was renamed as “Hypapante” probably by Hesychius of Jerusalem. This novelty was accorded with a brilliant Armenian “Տեառնընդառաջ” adaptation. Nevertheless, Church fathers apparently were not satisfied or yet were forced to propose a new one-of-a-kind name for the feast, in the form of “The coming of forty-days old Christ to the Temple”. The most plausible explanation for this course of action was the imminent threat by Nestorians, well active in the south of Armenia, who would vehemently reject the divine nature of Jesus.
Keywords: Կրօն; Ծիսակատարութիւններ